(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Several studies and investigations have attempted to introduce a new design for the conventional distribution networks. This proposed design aims to offer a reduction in substation installation cost and in power losses by eliminating some voltage levels in networks. Sine, this is difficult to achieve with conventional distribution networks, when the conventional cables and transformers are used, where the impedance of conventional equipment is high. Due to High-Temperature Superconductor (HTS) materials provide extremely low impedance to AC when cooled to the boiling point of liquid nitrogen (77K), the interest in using HTS materials to produce power cables and transformers is increased. The present paper investigates the practical impacts of installing HTS cables and transformers and seeks to introduce a future network design which leads to the best implementation for superconducting networks, thus, a drop in the substation installation cost and energy losses cost by eliminating some voltage levels in the traditional networks.